“Theology and public life” The knowledge of God and the service of others (Hekima Review, 2014)
What has theology to do with public life? Based on the fact that theology seeks to verbalize faith, to help faith to speak meaningfully and intelligibility – and above all faithfully – about the reality of God acting in creation, this article discusses the relationship between faith and public life, for a responsible and engaged faith. We would like to argue that the Christian believer’s engagement in public life from the particular perspective of the theological understanding of Christian faith, aims to create an impact in the transformation of human conditions in its integrality, a sincere adherence to the vision of the Kingdom of God that the Gospel holds forth to us. For that, our goal is to explain how a ‘theology of public life’, can become a ground of Christian public engagement, by debating the relationship between theology and public life, in such a way that the understanding of what faith may lead to a task-oriented. Moreover, theology has a vital public service to perform – a service which must be performed again and again, to respond to the Christian’s real-life-questions.